Nazarét and nazōrai͂os in the Gospel of John: The Johannine Jesus as a Nazirite? - Tops, Thomas (Zeitschrift für die neutestamentliche Wissenschaft, 2024)
The article examines the meaning of the words Ναζαρέτ and ναζωραῖος in the Fourth Gospel. It argues that the first word plays an important role in the incarnational logic of the Gospel, while the second word is significant for John’s Christology. Through the literary device of reader entrapment, John corrects the reader’s initial misjudgement that ὁ ναζωραῖος in John 18,5.7; 19,19 depicts Jesus as coming from Nazareth. To explain the Christological significance of this phrase, the article evaluates the thesis that ναζωραῖος characterises Jesus as a Nazirite. For instance, it compares the literary characterisation of the Johannine Jesus to the Nazirite rule in Num 6,1-21 and its reception in late Second Temple sources.